PENGELOLAAN DANA INFAQ ASN KABUPATEN PIDIE - Hendra, Arifan; Nufiar, Nufiar; Mariana, Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This research aims to understand and analyze the management of infaq funds in Pidie Regency. The research method used is a qualitative method, which allows researchers to gain in-depth insight into the topic. In collecting data, the author used various approaches, including library research methods and field research methods. The research results show that the management of infaq funds by the State Civil Apparatus (ASN) in Pidie Regency is a process that requires compliance with regulations and ethical principles, as well as high transparency. Even though ASN has complied with government regulations regarding the management of infaq funds, there are several aspects that need to be improved. Management of distribution of infaq funds is considered to be still not on target, and these funds have not been able to effectively increase community economic empowerment.